Changes in infection-related hospitalizations in children following pandemic restrictions: an interrupted time-series analysis of total population data. (31st May 2021) - Todd, Isobel M F; Miller, Jessica E; Rowe, Stacey L; Burgner, David P; Sullivan, Sheena G
Abstract: Background: Infectious diseases are a leading cause of hospitalization during childhood. The various mitigation strategies implemented to control the coronavirus disease (COVID-19) pandemic could have additional, unintended benefits for limiting the spread of other infectious diseases and their associated burden on the health care system. Methods: We conducted an interrupted time-series analysis using population-wide hospitalization data for the state of Victoria, Australia. Infection-related hospitalizations for children and adolescents (aged <18 years, total source population ∼1.4 million) were extracted using pre-defined International Classification of Diseases 10 th Revision Australian Modification (ICD-10-AM) codes. The change in weekly hospitalization rates (incidence rate ratio, IRR) for all infections following the introduction of pandemic-related restrictions from 15 March 2020 was estimated. Results: Over 2015–19, the mean annual incidence of hospitalization with infection among children less than 18 years was 37 per 1000 population. There was an estimated 65% (95% CI 62-67%) reduction in the incidence of overall infection-related hospitalizations associated with the introduction of pandemic restrictions. The reduction was most marked in younger children (at least 66% in those less than 5 years of age) and for lower respiratory tract infections (relative reduction 85%, 95% CI 85-86%). Conclusions: The wider impacts of pandemic mitigation strategies on non-COVID-19 infection-related hospitalizations are poorly understood. We observed marked and rapid decreases in hospitalized childhood infection. In tandem with broader consequences, sustainable measures, such as improved hand hygiene, could reduce the burden of severe childhood infection post-pandemic and the social and economic costs of hospitalization.